2001
DOI: 10.1159/000047820
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Guanine Nucleotide Binding Protein Alpha-Subunit Receptor Coupling in GH Cell Lines: <i>Effects of Bromocriptine and Hormones on Effector Enzyme Modulation</i>

Abstract: The purpose of the present study was to elucidate how the dopamine agonist bromocriptine affected receptor-effector systems in GH cells by measuring adenylate cyclase (AC) and phospholipase C (PL-C) modulation in cell membrane preparations. To perturb the interaction between the receptor and G-protein, polyclonal antibodies reacting with the predicted C-terminal amino acid sequence of G-protein α-subunits were used. The effect of bromocriptine on secretagogue elicited prolactin (PRL) secretion from whole cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…With respect to pituitary function, patients with inactivating GNAS mutations show variable degrees of GHRH resistance (415), GH deficiency (210), or hypoprolactinemia (88). In accordance with the important role of G s family G proteins in lactotrophs and somatotrophs, hypothalamic inhibiting hormones, like dopamine or somatostatin, act through G i -coupled receptors (311,536).…”
Section: A Hypothalamo-pituitary Systemmentioning
confidence: 99%
“…With respect to pituitary function, patients with inactivating GNAS mutations show variable degrees of GHRH resistance (415), GH deficiency (210), or hypoprolactinemia (88). In accordance with the important role of G s family G proteins in lactotrophs and somatotrophs, hypothalamic inhibiting hormones, like dopamine or somatostatin, act through G i -coupled receptors (311,536).…”
Section: A Hypothalamo-pituitary Systemmentioning
confidence: 99%
“…Bromocriptine acts on dopamine D2 receptors which are also present in the pituitary (43). The detailed molecular actions of bromocriptine (2-bromo-alphaergocryptine), a semi-synthetic ergot alkaloid with long-term stimulatory effects on dopamine D2 receptors, are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, Gβγ dimers also contribute to the regulation of various effectors. Previous studies have shown that TRH-R is quite promiscuous, coupling predominantly to G q/11 but also interacting with G s and G i proteins in GH3 cells ( Paulssen et al, 1992a ; Johansen et al, 2001b ; Boutin et al, 2012 ). Binding of a ligand to TRH-R results in an exchange of GDP for GTP at the Gα subunit.…”
Section: Thyrotropin-releasing Hormone Receptor-mediated Signalingmentioning
confidence: 98%
“…Nevertheless, TRH-R turned out to be able to activate more than one second messenger system under certain circumstances. In addition to the G q/11 -regulated PLC pathway, TRH-R may also activate AC through direct interaction with the stimulatory G s protein ( Paulssen et al, 1992a ; Johansen et al, 2001b ). In addition, there is some evidence from experiments with GH3 cells that TRH-R can couple to the inhibitory G i proteins that do not cause activation of AC ( Paulssen et al, 1992a ).…”
Section: Thyrotropin-releasing Hormone Receptor-mediated Signalingmentioning
confidence: 99%